FOUNDING FATHER PERUMUSAN DIMENSI MODERASI FIQH ISLAM: Studi Hukum Kelurga Islam Bidang Perkawinan di Indonesia dari Orde Baru Menuju Pasca Reformasi - Sadari, Sadari (Moderation | Journal of Islamic Studies Review, 2021)
Abstract: This article has the dimension of Fiqh in highlighting the context of Islamic family law whose locus is in Indonesia because it is suspected that it still has contra-legality of the law. This is due to: first, the level of diversity (heterogeneity), second, differences in the meaning of religious law between the majority of Indonesian Muslims who accept the presence of other religions, third, still have legal anomalies, fourth, the Indonesian system adheres to multi-religions, fifth, there is legal unification in Indonesia, sixth, has complex and complicated issues, especially in contemporary affairs in the fields of human rights, democracy, nation-state, civil society and constitutionalism. Along with the swift flow of globalization, the six reasons above have great potential to sweep away Islamic family law in Indonesia. Therefore, it is necessary to moderate the dimensions of Islamic fiqh which have relevance, namely by tracing the founding fathers of the formulation of Islamic family law in Indonesia from the era of the New Order era to the post-reform era.